دور البنك المركزي والبنوك التجارية في دعم وتيرة الشمول المالي –دراسة بعض التجارب العربية- (Journal of Economics and Management Research, 2023)
ملخص: تهدف هذه الدراسة إلى إبراز الدور المهم للبنوك المركزية وتجارية في تعزيز ودعم الشمول المالي، من حيث استعراض جهود البنوك المركزية والبنوك التجارية في تحقيق وتعزيز الشمول المالي وتحليل بعض المؤشرات للشمول المالي. وقد توصلت الدراسة إلى أن البنوك التجارية والبنك المركزي تلعب دورا هاما في تعزيز تطبيق الشمول المالي في محاولة لإيصال الخدمات المالية الى كافة الفئات والأماكن مما يزيد من فرص إتاحة الادخار والاستثمار للجميع. وأن الدول العربية لا تزال متأخرة كمجموعة في تحسين كفاءة وصول الخدمات المالية والمصرفية إلى مختلف فئات المجتمع وخاصة المرأة. Abstract: This study aims at highlighting the important role of central banks and commercial banks of enhancing financial inclusion, in terms of reviewing the efforts of central banks and commercial banks in achieving and enhancing financial inclusion and analyzing some indicators of financial inclusion. The study found that commercial banks and central banks play an important role in enhancing the application of financial inclusion to deliver financial services to all groups and places, increasing the opportunities for saving and investment for all. And that Arab countries are still lagging behind in improving the efficiency of financial and banking services access to various segments of society especially women.